Cyclisation reactions for the synthesis of natural and unnatural piperidines - Barat, Viktor (2017)
This work describes the platinum mediated ring opening isomerisation of 2,3-cyclopropanated piperidines, which results in either an endo or exocyclic olefin product. In the case where the beta-hydrogen is absent, a platinum-mediated Wagner-Meerwein type 1,2-alkyl shift reaction is observed. A serendipitous discovery during a cyclopropanation lead us to Prins reaction under extremely mils condition, furnishing piperidino-dioxanes with complete stereocontrol. This reaction inspires us to pursue the total synthesis of Lupin alkaloids, however it was not compatible with the target alkaloid structures. The total synthesis of (-)-cytisine was achieved using a stereodivergent 6-endo aza-Michael reaction, which can be utilized for the total synthesis of various piperidine and quinolizidine alkaloids. During the enantioselective synthesis, we have discovered that our system does not follow the Evans diastereoselective alkylation model, being the first reported example.